The Impact of Tutoring on Early Reading Achievement for Children With and Without Attention Problems - Rabiner, David L. (2004)
This study examined whether the benefits of reading tutoring in first grade were moderated by children’s level of attention problems. Participants were 581 children from the intervention and control samples of Fast Track, a longitudinal multisite investigation of the development and prevention of conduct problems. Standardized reading achievement measures were administered after kindergarten and 1st grade, and teacher ratings of attention problems were obtained during 1st grade. During 1st grade, intervention participants received three 30-min tutoring sessions per week to promote the development of initial reading skills. Results replicated prior findings that attention problems predict reduced 1st grade reading achievement, even after controlling for IQ and earlier reading ability. Intervention was associated with modest reading achievement benefits for inattentive children without early reading difficulties, and substantial benefits for children with early reading difficulties who were not inattentive. It had no discernible impact, however, for children who were both inattentive and poor early readers. Results underscore the need to develop effective academic interventions for inattentive children, particularly for those with co-occurring reading difficulties.